Szanujący się dziennikarz, kraj, film… On selected instances of the participle szanujący się (‘self-respecting’) in contemporary Polish - Lisczyk, Karolina (Papers in Linguistics, 2022)
The aim of the article is to determine what Polish speakers mean by using the participle szanujący się (‘self-respecting’). The undertaken study included 3,358 sentences containing the word taken from the MoncoPL monitoring corpus. The material was divided into eleven groups, distinguished according to the connectivity of the examined participle with nouns with a particular meaning. Based on the analyses, it was found that szanujący się is an indicator of stereotyping and, in some instances it has the same contextual meaning as adjectives typowy (‘typical’) and dobry (‘good’).